Altered adipocyte progenitor population and adipose-related gene profile in adipose tissue by long-term high-fat diet in mice - Xu, Xiaohua (2012)
AIMS: High-fat diet (HFD) is associated with adipose inflammation, which contributes to key components of metabolic abnormalities. The expanded adipose tissue mass associated with obesity is the result of hyperplasia and hypertrophy of adipocytes. In this study, we investigated the effects of long-term HFD on adipocyte progenitor cell (APC) population and adipose-specific gene profiles in both white and brown adipose, and the role of perivascular adipose in the alteration of vascular function in response to HFD. MAIN METHODS: Male C57BL/6 mice were fed a standard normal diet (ND) or HFD for about 8 months. Glucose metabolism was assessed by an intraperitoneal glucose tolerance test. APC population and adipose-related gene profile were evaluated, and vascular function was measured in the presence or absence of perivascular adipose. Adiponectin and AMPK activity were also investigated. KEY FINDINGS: HFD induced insulin resistance and glucose intolerance, and resulted in a decrease in APC population in brown, but not in white adipose tissue, when compared with animals fed a ND, with differential alterations of white and brown adipocyte-specific gene expression in brown and white adipose. Additionally, HFD led to altered vascular function in arteries in the presence of perivascular adipose tissue, which is associated with increased superoxide production. Adiponectin and AMPK activity were significantly decreased in response to long-term HFD. SIGNIFICANCE: These findings suggest that long-term high-fat intake differentially alters adipocyte progenitor population and adipose-related gene expression in adipose tissue, and adiponectin-AMPK signaling might be involved. In addition, HFD induces changes in perivascular adipose-mediated vascular function.